2021
DOI: 10.3389/fpsyg.2020.567230
|View full text |Cite
|
Sign up to set email alerts
|

Patients Living With Breast Cancer During the Coronavirus Pandemic: The Role of Family Resilience, Coping Flexibility, and Locus of Control on Affective Responses

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has strongly affected oncology patients. Many screening and treatment programs have been postponed or canceled, and such patients also experience fear of increased risk of exposure to the virus. In many cases, locus of control, coping flexibility, and perception of a supportive environment, specifically family resilience, can allow for positive emotional outcomes for individuals managing complex health conditions like cancer. This study aims to determine if fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 70 publications
3
32
0
5
Order By: Relevance
“…Due to the pandemic, cancer patients were at risk of disruption of treatment at medical facilities [ 15 , 40 ], particularly when hospitals were burdened with high volumes of COVID-19 patients [ 28 , 41 ]. Some facilities revised chemotherapy protocols to minimize both the frequency of chemotherapy visits and the degree of immunosuppression [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the pandemic, cancer patients were at risk of disruption of treatment at medical facilities [ 15 , 40 ], particularly when hospitals were burdened with high volumes of COVID-19 patients [ 28 , 41 ]. Some facilities revised chemotherapy protocols to minimize both the frequency of chemotherapy visits and the degree of immunosuppression [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study surveyed lung cancer patients who reported anxiety with reasons for anxiety as fear of delaying testing, and fear of contracting the virus, and found a higher than normal percentage of patients who needed referrals to some level of mental health services [ 45 ]. Breast cancer patients experienced fear of increased risk of COVID-19 exposure, but an Italian study found that family resilience, coping flexibility, and feeling in control contributed significantly in managing their cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of adaptive cognitive skills and social support perception is particularly useful over the current COVID-19 pandemic and its related mental health issues (Marazziti et al, 2020), particularly worrying for people with cancer experience (Renzi et al, 2019;Brivio et al, 2021a). Wang et al (2020) evidenced that cancer patients tend to show a higher level of anxiety, distress, and depression compared to the healthy population, as shown in Italy by Brivio et al (2021b).…”
Section: Introductionmentioning
confidence: 99%
“…The PACT displayed adequate reliability and validity across Israeli and American samples ( Bonanno et al, 2011 ), demonstrating cross-cultural adequacy. It has been mainly used in studies of coping in highly trauma-exposed samples ( Bonanno et al, 2011 ; Park et al, 2015 ; Bartholomew et al, 2017 ; Pinciotti et al, 2017 ; Sullivan and Wade, 2019 ), in potentially traumatic life events such as adjustment to college ( Bonanno et al, 2011 ; Galatzer-Levy et al, 2012 ; Saita et al, 2017 ), grief severity in older widows and widowers ( Knowles and O’Connor, 2015 ), experience with the COVID-19 pandemic ( Zhou et al, 2020 ; Brivio et al, 2021 ), and in breast cancer patients ( Hamama-Raz et al, 2012 ; Pat-Horenczyk et al, 2016 ; Brivio et al, 2021 ). The present study aimed to adapt the European Portuguese version of the PACT scale and validate it for patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%